An investigation of the relationship between the amount of extra-textual data and the quality of Wikipedia articles - Himoro, Marcelo Yuji; Hanada, Raíza; Cristo, Marco; Pimentel, Maria da Graça Campos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
Wikipedia, a web-based collaboratively maintained free encyclopedia, is emerging as one of the most important websites on the internet. However, its openness raises many concerns about the quality of the articles and how to assess it automatically. In the Portuguese-speaking Wikipedia, articles can be rated by bots and by the community. In this paper, we investigate the correlation between these ratings and the count of media items (namely images and sounds) through a series of experiments. Our results show that article ratings and the count of media items are correlated.